Open spaces in the castle of Veszprém - Csuka, Veronika (4D Journal of Landscape Architecture and Garden Art, 2006)
The historical castle is situated in the centre of Veszprém, which is the most valuable part of the town. Nowadays, in the castle area, there are several resurrections. That’s why the review, the valuation of the open spaces and the reconstruction are significant questions.